The Impact of Varied Exposure Duration to ELF (Extremely Low Frequency) Magnetic Field on Old Rice (Oryza sativa L.) Seed Viability - Fahmi Azrial; Dwijowati Asih Saputri; Ika Listiana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The deterioration in the viability of rice seeds (Oryza sativa L.) during storage, frequently attributed to damage to the cell membrane and accumulation of reactive oxygen species (ROS), presents significant challenges for rice cultivation. ELF magnetic fields offer an eco-friendly solution by enhancing cellular responses and repairing membranes. This study investigated the impact of exposure to a 0.2 mT ELF magnetic field on the viability of 8-month-old aged rice seeds (Inpari 32 HDB variety) using a Completely Randomized Design (CRD) with four exposure durations: control (M0), 3 minutes 54 seconds (M1), 7 minutes 48 seconds (M2), and 11 minutes 42 seconds (M3), replicated four times. Results indicated significant improvements in viability, with M2 and M3 yielding optimal germination rates (98.00%, 97.50%), reduced mean germination time (2.47 days), and enhanced germination index (268.75). Radicle and plumule lengths also increased (6.95 cm and 4.82 cm, respectively). Although germination speed coefficient, germination time, and uniformity values (51.50–60.50%) showed only minor improvements, the results underscore the potential of ELF magnetic fields as a sustainable method to enhance aged rice seed viability, contributing to improved agricultural practices.